Graduate Students Metacognitive Reading Knowledge of Monitoring Strategies - Dwi Susanti; Furaidah Furaidah; Johannes Ananto Prayogo (Jurnal Pendidikan Humaniora, 2021)
Abstract: This study presents the graduate students’ understanding of metacognitive reading strategies. Obtained from thinking-aloud and interview, seven reading strategies are monitored when reading namely, (1) restating strategy to figure out the author’s meaning, (2) making gist conclusion to get the key point, (3) using Google translate to interpret new terms confidently, (4) Rereading to amplify self-understanding correction, (5) Using context clues to get complete idea of the point, (6) underlining to centralize reading points, and (7) Asking self-questions for rechecking comprehension. By noticing the strategies use and the reasons for its use, the students understand the appropriate strategies to use.Keywords: metacognitive reading knowledge, reading strategies, declarative-conditional knowledge, thinking-aloudAbstrak: Penelitian ini menyajikan pemahaman mahasiswa pascasarjana tentang strategi membaca metakognitif. Diperoleh dari thinking-aloud dan wawancara, tujuh strategi membaca yang dipantau saat membaca yaitu, (1) strategi mengulang untuk memahami makna penulis, (2) menyimpulkan inti bacaan untuk mendapatkan inti pembahasan, (3) menggunakan Google translate untuk menafsirkan istilah baru dengan percaya diri, (4) Membaca ulang untuk memperkuat koreksi pemahaman diri, (5) Membaca kontekstual untuk mengetahui info lengkap, (6) menggarisbawahi untuk memusatkan poin bacaan, dan (7) Mengajukan pertanyaan diri untuk memeriksa kembali pemahaman. Dengan memperhatikan strategi yang digunakan dan alasan penggunaanya, para siswa memahami strategi yang tepat untuk digunakan.Kata kunci: pengetahuan membaca metakognitif, strategi membaca, pengetahuan deklaratif-kondisional, berpikir-keras